Intenzívní psychiatrická péce o nemocné s psychogenními poruchami príjmu potravy - Faltus, F; Janecková, E; Papezová, H (Ceskoslovenska psychiatrie, 1992)
The authors summarize their therapeutic results in anorexia nervosa achieved at the unit of specialized care for eating disorders at the Psychiatric Clinic of the First Medical Faculty, Charles University, Prague. They find that applications for hospitalization of these patients have a rising trend and that in recent years in the unit mainly patients with severe forms of these diseases are admitted. During the past 7 years in the unit a total of 147 patients were hospitalized. By comprehensive regime treatment 84% of the patients with bulimia nervosa. As to basic symptoms, in bulimia nervosa the results were achieved in vomiting and bulimic attacks and in anorexia nervosa as regards appetite, hunger and general attitude to food. Finally the authors summarize the advantages of the unit specialized care for psychogenic eating disorders.
Keywords: Psychotherapy; Female; Adult; dospělí; bulimia; Humans; ženské pohlaví; Anorexia Nervosa; mentální anorexie; mužské pohlaví; lidé; psychoterapie; lidé středního věku; Male; Middle Aged; Adolescent; mladiství; Bulimia